Impact of Roux-en-Y Gastric Bypass on Mitochondrial Biogenesis and Dynamics in Leukocytes of Obese Women - Zaida Abad-Jiménez; Teresa Vezza; Sandra López-Domènech; Meylin Fernández-Reyes; Francisco Canet; Carlos Morillas; Segundo Ángel Gómez-Abril; Celia Bañuls; Víctor M. Víctor; Milagros Rocha (MDPI AG, 2022)
The chronic low-grade inflammation widely associated with obesity can lead to a prooxidant status that triggers mitochondrial dysfunction. To date, Roux-en-Y gastric bypass (RYGB) is considered the most effective strategy for obese patients. However, little is known about its molecular mechanisms. This interventional study aimed to investigate whether RYGB modulates oxidative stress, inflammation and mitochondrial dynamics in the leukocytes of 47 obese women at one year follow-up. We evaluated biochemical parameters and serum inflammatory cytokines -TNFα, IL6 and IL1β- to assess systemic status. Total superoxide production -dHe-, mitochondrial membrane potential -TMRM-, leucocyte protein expression of inflammation mediators -MCP1 and NF-kB-, antioxidant defence -GPX1-, mitochondrial regulation-PGC1α, TFAM, OXPHOS and MIEAP- and dynamics -MFN2, MNF1, OPA1, FIS1 and p-DRP1- were also determined. After RYGB, a significant reduction in superoxide and mitochondrial membrane potential was evident, while GPX1 content was significantly increased. Likewise, a marked upregulation of the transcription factors PGC1α and TFAM, complexes of the oxidative phosphorylation chain (I-V) and MIEAP and MFN1 was observed. We conclude that women undergoing RYGB benefit from an amelioration of their prooxidant and inflammatory status and an improvement in mitochondrial dynamics of their leukocytes, which is likely to have a positive effect on clinical outcome.